Effect of temperature, pH and calcium phosphate concentration on the properties of reassembled casein micelles - Fan, Zekun; Fehér, Bence; Hettinga, Kasper; Voets, Ilja K.; Bijl, Etske (Food hydrocolloids, 2024)
Reassembled casein micelles (RCMs) can be made by reassembling sodium caseinate with calcium and phosphate as well as other ions under controlled conditions into casein micelle-like structures. During the reassembly, the changes in processing parameters lead to differences in the properties of RCMs such as size, composition and structure. Understanding the effect of processing parameters on RCM properties is essential for their potential application in food products. However, the effect of process parameters has not been studied systematically. Therefore, the objective of this study was to evaluate the effect of temperature, pH and calcium phosphate concentration on the properties of reassembled casein micelles. The effect of pH on the size and structure of RCMs both during and after their formation was studied by dynamic light scattering and small-angle X-ray scattering. We found that pH affects both the size and internal structure of RCMs. We could also modulate the size and composition of RCMs by changing the temperature and calcium phosphate concentration. The insights of this study not only can be used to modulate the composition and structure of RCMs, but also help us to understand how processing parameters will influence the assembly of RCMs from novel sources, such as recombinant caseins.